Estudo sobre os métodos de diversidade para sistemas de TV digital - Rabaça, Ricardo Seriacopi (2017)
This project presents the history, basic information and advantages of using Software De ned Radio (SDR), diversity, layer division multiplexing (LDM) technique and the latest digital TV standards in a digital communication system. These subjects have been relevant in the scienti c community, making the project attractive in terms of the possibility of discoveries and optimizations. After that, the implementation of a digital communication system using these technologies is proposed. This implementation was performed by means of GRC simulation software and the use of C++ and Python programming languages. Therefore, it was necessary to test the steps of coding, modulation and digital transmission / reception. Finally, tests were performed with systems that use diversity, for example, Single-Input Single-Output (SISO), as well as setting Single-Input Multiple-Output (SIMO), using the settings 1x 2, 1x3 and 1x4, in order to compare possible advantages in spectrum utilization, data rate and system robustness to interference.